A web‐based mental health promotion intervention for pharmacy staff to reduce stigmatising and discriminating attitudes. (5th March 2018) - Wheeler, Amanda J.; Mey, Amary; Fowler, Jane L.; Mihala, Gabor; Kelly, Fiona
Abstract: Issue addressed: Stigma and discrimination can have a significant impact on successful mental health recovery. This research evaluated the effectiveness of a web‐based mental health promotion intervention on stigma and discrimination in community pharmacies via assessment of staff attitudes, confidence and skills. Methods: Guided by the intervention mapping framework, we used experiential learning techniques, including pre‐recorded consumer/carer narratives, role‐plays and panel discussions accessed by participants in an innovative, flexible, web‐based, program of modules. A quasi‐experimental pre‐post design was used to evaluate the intervention effectiveness. Participants completed pre‐ (T1) and post‐intervention (T2) questionnaires that contained both validated measures and questions developed or adapted specifically for this evaluation. Results: 566 pharmacy staff (357 pharmacists, 209 support staff) completed the intervention between September 2012 and May 2013; pharmacists completed eight online modules (4‐hours total), support staff completed four (2‐hours total). After participating, staff attitudes about mental health had changed in a positive direction; their confidence and skills when working with consumers and their carers had increased overall, although support staff remained less confident than pharmacists. Conclusion: These results suggest that the involvement of consumers and carers in the intervention development and delivery was integral to reducing pharmacy staff stigma and enhancing confidence and communication skills.